The effect of material property gradient on the fracture toughness of a PMMA/PC bimaterial with a crack normal to the interface - Shah, Qasim Hussain; Homma, H.; Iliyas, M. H.; Ismail, Ahmad Faris (Asian Network for Scientific Information, 2005)
Fracture toughness tests on CT specimens were carried out to study the fracture behavior for a crack lying perpendicular to the interface in a PMMA/PC bimaterial. Polymethylmethacrylate Acrylic (PMMA) and Polycarbonate (PC) cylindrical rods were joined together using the friction welding process. CT specimens were machined out of the bimaterial cylindrical rods. A sharp crack was introduced into the specimen perpendicular to and terminating at the bi-material interface. Specimens including monolithic and bi-material were loaded to fracture and experimental values of K were obtained. Finite element analysis was used to find out the stresses IC in the specimens. Subsequently the stress values were used to find out the fracture toughness of each specimen. It was found that the K values for bi-material specimen could not be achieved by utilizing the inverse IC square root singularity in stress but it was dependent upon Dundurs parameters for bi-materials.